Determinants of organizational practices and research culture for the enhancement of research performance in Malaysian universities - Esam, Asrizam; Ab Rahman, Suhaimi; Zawawi, Dahlia; Sazili, Awis Qurni; Ismail, Nik Rosniwati; Tugiran, Yusnita; Yusof, Yushaida; Kamarudin, Norliyana (Global Illuminators Malaysia, 2018)
Research performance is crucial to be monitored and maintained by the universities to make sure the output of research will meet the research output. Publication is one of the main research output to be measure to the research performance even though not all of the universities in Malaysia accomplish in publishing journals. Why there is dissimilar on every university researchers in research performance? This study explores the similarities and differences of organizational practices and research culture among academic staff that influence the research performance in Malaysia public university, mainly via a case study of Universiti Putra Malaysia , one of the best Research University particularly in agriculture fields in Malaysia. Qualitative approach was taken where 40 academic staff in science and technology groups and social science, art and humanities groups were interviewed through the focus group discussion. Views and experience from the researchers is crucial to determine their research performance factors. This study shows similarity of 5 possible tangible and 8 intangible factors that contribute to research performance emerging among the academic staff including one intangible factors as a new factors that will have an impact to the research performance. All the factors can be indicator as a benchmarking to others university especially new age of university in Malaysia. Primarily, it extends the literature, by providing further understanding on the issues of organizational practices and research culture on the Malaysian public universities.